Pilot Survey of Fuel Consumption in Rural Areas-III - Chandola, L. P.; Mahendra, A. K.; Ansari, M. Y. (Indian Forester, 1985)
Village Karaundi was surveyed for domestic fuel consumption in 1974 and again in 1983. Reduction in dung cake and running for Eucalyptus plantation without any outside Influence are the most useful and significant changes that have come to light in this recent survey. The effective dung cake consumption has been reduced from 37% to near 8% and firewood consumption from 33% to 23 % and increase in agricultural waste from 30% to 605 speaks very high of the rationality of villagers. Perhaps the daily rising costs of chemical fertilisers are responsible for this to some extent. The rational approach adopted by the farmers is confirmed by their outlook towards Eucalyptus. They saw’ the growth; liked it and planted Eucalyptus.